Pewarisan Keahlian Mendalang pada Keluarga Dalang Wayang Golek Abah Sunarya - Yuniar Wulan Dhari (Umbara, 2019)
This research discusses the process of skill inheritance on puppetry in the family of Abah Sunarya’s, a famous puppetry in Kampung Giri Harja, Jelekong, Kabupaten Bandung. This research applies qualitative approach in particular ethnography. Primary data were collected through participant observation and in-depth interview. This research suggests that the inheritance process has been carried out through socialization and enculturation. In the puppetry family, children undergo regular and consistent habitiatuin on puppetry show.  This process leads to the growing interest on puppetry, the show and the skill, and this leads to the growing sense of responsibility to preserve the family tradition. This research discusses the process of skill inheritance on puppetry in the family of Abah Sunarya’s, a famous puppetry in Kampung Giri Harja, Jelekong, Kabupaten Bandung. This research applies qualitative approach in particular ethnography. Primary data were collected through participant observation and in-depth interview. This research suggests that the inheritance process has been carried out through socialization and enculturation. In the puppetry family, children undergo regular and consistent habitiatuin on puppetry show.  This process leads to the growing interest on puppetry, the show and the skill, and this leads to the growing sense of responsibility to preserve the family tradition.